Determinan Keputusan Pembelian melalui Kesadaran Halal: Studi Empiris terhadap Konsumen Muslim di Lima Restoran Sushi Jepang Provinsi DKI Jakarta - Dian Nofiana (Studia Economica : Jurnal Ekonomi Islam, 2026)
This study aims to analyze how halal product knowledge, halal certification, religiosity and electronic word of mouth indirectly through halal awareness, on purchasing decisions in sushi restaurants, both simultaneously and partially. This study also aims to identify the variables that have the strongest influence on purchasing decisions. This study uses primary data in the form of questionnaires containing statements related to the variables studied to Muslim consumers of five Japanese sushi restaurants in DKI Jakarta province as respondents. This study uses SEM-PLS analysis with a sampling technique using non-probability sampling with a purposive sampling method to 200 respondents, assisted by the SmartPLS 4 statistical tool. The results of this study indicate that the variables of halal product knowledge, halal certification and religiosity have a significant effect on halal awareness, while the electronic word of mouth variable does not. The results also show that the religiosity variable is the most influential or dominant variable on halal awareness and the halal awareness variable has a significant effect on purchasing decisions in Japanese sushi restaurants in DKI Jakarta province